2014
DOI: 10.1515/pac-2014-5010
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor nanowire solar cells: synthetic advances and tunable properties

Abstract: Abstract:The solar power received by Earth far exceeds global power demands. Despite this, infrastructure shortages and high capital costs prevent the wide-scale adoption of photovoltaics to displace conventional energy technologies relying on carbon-based fuels. In response, new concepts and materials have been explored to develop next-generation solar cells capable of operating more efficiently and cheaply. Over the past decade, single semiconductor nanowire (NW) and NW array devices have emerged as promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
1
5
0
1
Order By: Relevance
“…Large-area compositional depth profiling of the array by secondary-ion mass spectroscopy (SIMS) reveals a uniform P concentration profile across the depth of the trenches comprising the superlattice (Figure c). Taking the measured average P concentration of 7 × 10 18 dopants/cm 3 and correcting for the 8% fill factor of the trench-filled area relative to the total sample sputtered area (Supplementary Materials and Methods and the Supporting Information), we estimate the P doping to be at the level of 8.8 × 10 19 dopants/cm 3 , which is comparable to P dopant concentrations observed in VLS-grown nanowires. , Together, these data confirm that superlattices bearing multiple parallel Si p–n junctions can be rapidly prepared through the tandem n-type filling of trenches in p-type Si substrates. We note that the Au expelled from the trenches after they fill with Si can be readily removed (e.g., through wet etching in KI/I 3 – ) and reclaimed for future reuse.…”
Section: Introductionsupporting
confidence: 61%
“…Large-area compositional depth profiling of the array by secondary-ion mass spectroscopy (SIMS) reveals a uniform P concentration profile across the depth of the trenches comprising the superlattice (Figure c). Taking the measured average P concentration of 7 × 10 18 dopants/cm 3 and correcting for the 8% fill factor of the trench-filled area relative to the total sample sputtered area (Supplementary Materials and Methods and the Supporting Information), we estimate the P doping to be at the level of 8.8 × 10 19 dopants/cm 3 , which is comparable to P dopant concentrations observed in VLS-grown nanowires. , Together, these data confirm that superlattices bearing multiple parallel Si p–n junctions can be rapidly prepared through the tandem n-type filling of trenches in p-type Si substrates. We note that the Au expelled from the trenches after they fill with Si can be readily removed (e.g., through wet etching in KI/I 3 – ) and reclaimed for future reuse.…”
Section: Introductionsupporting
confidence: 61%
“…, 1D) can elicit quantum confinement effects that in turn dictate key material properties. , For example, previous efforts have demonstrated that 1D semiconductors ( e.g. , nanowires) can be prepared using bottom-up chemical approaches and tailored to exhibit a panoply of unique properties relevant to photonics, electronics, spintronics, catalysis, biophysics, and photovoltaic energy conversion. Moreover, shortly after graphene took the condensed matter physics community by storm, many leading research groups directed their efforts to the preparation and study of dimensionally restricted variants of graphene, notably graphene nanoribbons (GNRs). In 2007, Han et al observed that the band gap energy in lithographically patterned GNRs can be systematically tuned by changing the GNR width, thereby setting in motion a broad-based effort focused on discovery of new low-dimensional condensed matter systems (Figure a) . Soon after, Dai and co-workers demonstrated a highly tunable field-effect mobility in GNR devices (Figure (b)). ,, …”
Section: D Tmds: Achievements and Featuresmentioning
confidence: 99%
“…III–V triple-junction thin films monolithically integrated on a standard Si wafer have also been demonstrated recently with an efficiency of 33.3% . To increase the efficiency of multijunction solar cell devices, III–V NWs (NWs) monolithically integrated on Si substrate could be employed. NWs are high-aspect-ratio crystalline structures that, when implemented on a Si platform, would allow to significantly reduce III–V material usage and the associated cost and at the same time ensure an extremely high absorption of light thanks to the optimal coupling. Additionally, the small interface area of the NWs is very effective at minimizing stresses commonly arising during the epitaxial growth of lattice and thermal mismatched thin films. Thus, the efficient strain relaxation in thin NWs allows extending the possible material combinations needed to grow NW heterostructures. …”
Section: Introductionmentioning
confidence: 99%